Problems of reforming and modernizing the higher education system in Ukraine (socio-philosophical analysis) - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes various aspects of the problem of reforming and modernizing the higher education system in Ukraine in conditions of information society.